A power conversion chain with an internally-set voltage reference and reusing the power receiver coil for wireless bio-implants. (April 2018) - Barati, Mahdi; Yavari, Mohammad
Abstract: In this paper, a power conversion chain (PCC) with an internally-set voltage reference is presented. It is comprised of a power receiver coil, an active rectifier and a novel buck-boost converter. The output voltage of the PCC is set by using the parameters of a new buck-boost converter control unit in order to avoid utilizing an extra voltage reference circuit. Furthermore, the proposed PCC reuses the power receiver coil to facilitate the realization of the buck-boost converter. This way, the efficiency of the proposed PCC gets almost independent of the receiving coil voltage amplitude. In addition, the proposed buck-boost converter significantly reduces the size of the PCC and makes it suitable for wireless power transfer via inductive links in bio-implant applications. It should be noted that employing an active rectifier followed by the proposed buck-boost converter enhances the PCC end-to-end efficiency. The proposed PCC is simulated for the input received signal with a frequency of 10 MHz and an amplitude variation within 3–7 V. The simulation results show that the efficiency variation is less than 2.6% and the achieved maximum efficiency is 80.4% and 63.4% for the proposed converter and PCC, respectively. For further verification of the proposed idea, a proof-of-concept prototype is implemented and experimental results are provided.